Innovation and Design of a Web-Based Pain Education Interprofessional Resource - Leila Lax; Judy Watt-Watson; Michelle Lui; Adam Dubrowski; Michael McGillion; Judith Hunter; Cameron MacLennan; Kerry Knickle; Anja Robb; Jaime Lapeyre (Pain Research and Management)
INTRODUCTION: The present article describes educational innovation processes and design of a web-based pain interprofessional resource for prelicensure health science students in universities across Canada. Operationalization of educational theory in design coupled with formative evaluation of design are discussed, along with strategies that support collaborative innovation.